Epstein Barr Virus (EBV) Latent Membrane Protein 1 (LMP-1) Regulates Functional Markers in Intermediate and Non-Classical Monocytes - Moyano, Agustina Ayelén (2024)
Background: The Epstein?Barr virus (EBV) infects more than 90 percent of the humanpopulation. In pediatric patients, the innate immune response against EBV primary infection plays akey role. Monocytes and macrophages can have distinct functions depending on the microenvironment surrounding them. At least three monocyte subpopulations can be differentiated depending onmembrane protein expression: classical (C, CD14++CD16−), intermediate (I, CD14++CD16+), andnon-classical (NC, CD14+CD16++). They also modulate T and B lymphocyte activation/inhibitionthrough the expression of costimulatory molecules such as CD80, CD86, and PD-L1. Yet, little isknown about monocytes? role in EBV infection. Methods: Peripheral blood and tonsil biopsies of EBVprimary infected (PI) patients, healthy carriers (HCs), and patients undergoing reactivation (R) werestudied. Results: Classical monocytes prevailed in all infectious statuses. Tonsillar CD163 positivelycorrelated with CD163 expression in NC monocytes in HCs. PD-L1+ cells in the tonsil positivelycorrelated with PD-L1 expression in NC monocytes. LMP-1 viral latent protein presented a positivecorrelation with PD-L1, CD163, and CD206 expression in the NC subpopulation. Conclusions: Ourresults evidence the predominant role of I and NC monocytes? response against EBV infection. Furthermore, the viral oncoprotein LMP-1 could be involved in the expression of regulatory proteins in Iand NC monocytes